The Portuguese version of the CORE-OM: translation, adaptation, and preliminary study of psychometric properties (Archives of Clinical Psychiatry, 2012)
BACKGROUND: The Clinical Outcome Routine Evaluation - Outcome Measure (CORE-OM) is a European self-report measure of psychological well-being in adults, which is already adapted for more than 20 countries. The CORE-OM is applicable in primary care settings, in occupational health and educational contexts, as well as for evaluations of mental health services quality. OBJECTIVES: To translate the CORE-OM into and adapt it to the Portuguese language. METHODS: The translation of CORE-OM to Portuguese was conducted in accordance with the CORE System Trust international guidelines, in collaboration with the authors of the original CORE-OM. This guidelines involved seven independent translations by individuals familiar/non-familiar with the field of mental health and by licensed translators. After the discussion of these translations in a focus group, a final version of the Portuguese CORE-OM was established. Individuals from different age groups, socio-cultural backgrounds and educational levels participated in this translation process. RESULTS: Preliminary results in a sample of 111 individuals (general population) show that the translated measure is confidential and has a good internal reliability. DISCUSSION: The Portuguese version of the CORE-OM is a valid and adequate instrument to evaluate psychological changes, both in research and clinical practice contexts.